Adducin and plasminogen activator inhibitor 1 gene polymorphisms in coronary artery bypass surgery - Kargun, Kursat; Senol, Sefa; Secen, Ozlem; Ayaz-Tuylu, Berrin (Parlar Scientific Publications, 2018)
In this study, coronary artery patients involved in a coronary artery bypass graft (CABG) and a control group displaying no coronary artery disease (CAD) are being compared in terms of alpha adducin Gly460Trp and plasminogen activator inhibitor 1 (PAI-1) gene polymorphisms. Ninety patients (64 men, 26 women; average age: 59.8 ± 9.2) who were recommended for a coronary artery bypass graft because of their coronary artery disease and 80 healthy people (57 men, 23 women; average age: 58.3 ± 7.4) who were not coronary artery patients were included in this study. Within these samples, adducin Gly460Trp and plasminogen activator inhibitors 1 (PAI-1) gene polymorphisms were determined by the real time polymerase chain reaction method. According to the obtained results, in the comparison between the coronary artery bypass graft group and the control group, there were no statistically significant differences in terms of adducin Gly460Trp and plasminogen activator inhibitor 1 (PAI-1) gene polymorphisms (p>0.05). In this study, it was concluded that the interpretation of adducin Gly460Trp and plasminogen activator inhibitor 1 (PAI-1) gene polymorphisms as being risk factors for development and up development of coronary artery diseases can't be substatiated. Especially in patients with coronary artery adducin and plasminogen activator inhibitor-1 gene polymorphism else think it would be more useful to be evaluated. © by PSP.
Keywords: Adducin; Coronary artery disease; Gene polymorphism; Plasminogen activator inhibitor 1